2009
DOI: 10.1007/s12575-009-9021-0
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Guide to Rodent Islet Isolation and Assessment

Abstract: Pancreatic islets of Langerhans secrete hormones that are vital to the regulation of blood glucose and are, therefore, a key focus of diabetes research. Purifying viable and functional islets from the pancreas for study is an intricate process. This review highlights the key elements involved with mouse and rat islet isolation, including choices of collagenase, the collagenase digestion process, purification of islets using a density gradient, and islet culture conditions. In addition, this paper reviews commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
190
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(197 citation statements)
references
References 53 publications
6
190
0
1
Order By: Relevance
“…However, islets in this work were healthy, with a SI between 2 and 20 (Carter et al 2009) not showing any harmful effect of Histopaque on the islets, as supported also by more recent studies performed with Ficoll-based gradients (McCall et al 2011;Mita et al 2010;Lamb et al 2011), nor were any statistical differences between methods observed. However, although GSIS is an important predictor of islet function it does not have a correlation with clinical transplantation outcomes (Ricordi et al 2001;Street et al 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, islets in this work were healthy, with a SI between 2 and 20 (Carter et al 2009) not showing any harmful effect of Histopaque on the islets, as supported also by more recent studies performed with Ficoll-based gradients (McCall et al 2011;Mita et al 2010;Lamb et al 2011), nor were any statistical differences between methods observed. However, although GSIS is an important predictor of islet function it does not have a correlation with clinical transplantation outcomes (Ricordi et al 2001;Street et al 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Islet function is defined by its ability to regulate the release of insulin and other hormones in response to changes in extracellular glucose concentration (Carter et al 2009). Therefore, GSIS provides an accepted measure of islet function and, consequently, of the quality of the preparation.…”
Section: Discussionmentioning
confidence: 99%
“…The cell suspension was centrifuged at 1,500 rpm for 4 min, the precipitated cells were re -suspended in HBSS solution, passed through a 100-Ī¼m cell strainer (BD Biosciences, San Jose, CA, USA), and collected into a 10 -cm dish. Pancreatic islets were handpicked and cultured at 37" !under a humidified atmosphere of 5% CO2 and 95% air in islet medium (RPMI-1640 medium containing 2.0 g/l NaHCO3, 10 mM HEPES solution, 50 Ī¼M 2 -mercaptoethanol, 1 mM sodium pyruvate, 10% FBS, 100 IU/ml penicillin, and 50 Ī¼g/ml streptomycin) (22).…”
Section: Pancreatic Islet Isolationmentioning
confidence: 99%
“…Islets were isolated from pancreas of rats by collagenase V digestion and Ficoll 400 step density gradient separation as described (Cherif et al 1998, Carter et al 2009, Li et al 2009). …”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%